The WHO Clean Care is Safer Care programme: Field-testing to enhance sustainability and spread of hand hygiene improvements - Didier Pittet; Benedetta Allegranzi; Julie Storr (Elsevier, 2008)
Summary: The World Alliance for Patient Safety is an evolving programme of the WHO, established to raise the profile of patient safety within the global health care agenda. The decision taken in 2004 to focus the effort and attention of the First Global Patient Safety Challenge on the problem of health care-associated infection (HAI) is testimony to the fact that HAI is a significant patient safety hazard and continues to harm patients in the 21st century. Much of this harm is avoidable through better application of measures which already exist including universal implementation of hand hygiene improvement methods. Action on hand hygiene improvement is therefore at the core of the First Challenge, and field testing of the WHO implementation strategies developed in conjunction with the WHO Guidelines on Hand Hygiene in Health Care (Advanced Draft) is on track to complete by the end of 2008. Following this, a revised and updated guideline and suite of implementation tools will be published by the WHO. It is important to note that the First Global Patient Safety Challenge has mobilized an unprecedented number of countries over a short timeframe to commit to take action on HAI. Keywords: Hand hygiene, Improvement, WHO, Clean Care is Safer Care, Sustainability, Cross infection, Health care-associated infection, Public health